The role of local content policy in local value creation in Nigeria's oil industry: a structural equation modeling (SEM) approach - Niran, Adedeji Abdulkabir; Ahmad Sidique, Shaufique Fahmi; Abd Rahman, Azmawani; Law, Siong Hook (Elsevier, 2016)
The question of how adopting local content policy (LC policy) benefits the economic growth of developing oil-rich countries is hardly new but is a continuous debate that often centers on increasing the value-added that LC policy can create within the oil industry. However, the level to which LC policy can achieve this goal in some of these countries has not yet been ascertained. In Nigeria, the impact of LC policy on local value creation has generated divergent speculation. This study addresses this gap by assessing the impact of LC policy in influencing local value creation with particular reference to indigenous oil firms’ participation, backward linkages and job creation. Structural equation modeling (SEM) technique was applied to analyze the data obtained from a survey of 209 local oil and gas firms in the Niger Delta. Our findings confirm that LC policy has a positive and significant impact on local value creation. However, we found that local value created in the Nigerian oil industry as a consequence of LC policy is lower than the expected target. This implies that the implementation of the policy needs to be closely monitored to ensure its efficacy towards increasing economic development.